Feracrylum –A Haemostatic Becomes a Boon for Treating Chronic Periodontitis In Patients Under Anti-Coagulant Therapy - Janardhan, Karthika; Parikh, Hiral (Journal of Neonatal Surgery, 2025)
Background:Chronic periodontitis is an inflammatory disease of many origins that compromises tooth-supporting structures.(1,2) Patients with bleeding tendencies usually have compromised periodontal health.(1,2,3,4) While scaling and root planing (SRP) remains the main stay of non-surgical management, adjunctive drug delivery agents can enhance therapeutic outcomes. Patients with compromised bleeding and coagulation pathways are usually unable to receive optimum dental treatment often. Feracrylum, a lesser-explored topical hemostatic with antimicrobial properties, may be an ideal agent which can be utilized in such patients to provide supportive periodontal therapy.(3,4) Aim:To determine the efficacy of Feracrylum in the management of chronic periodontitis, in patients under anti-coagulant therapy. Materials and Methods:A total of 30 patients, undergoing anti-coagulant therapy, with associated chronic periodontitis were randomized into two groups, after acquiring informed consent and cardiologist consultation. Taking into account the dropouts in the study, the final count of patients in each group were as follows: Feracrylum (n=13) and Control (SRP + saline, n=12). Intervention was as follows, Feracrylum group, received oral prophylaxis and subingival irrigation of 1% Feracrylum, while the control group received saline irrigation. Both groups were advised regarding chemical plaque control with 1% feracrylum mouthwash and saline mouth rinse respectively. Clinical parameters including probing pocket depth (PPD), clinical attachment level (CAL), plaque index (PI), and modified sulcus bleeding index (MSBI) were recorded at baseline and one month post-treatment respectively. Subgingival plaque samples were tested for the presence of red complex organisms with BANA enzymatic test. Results:The Feracrylum group exhibited a significant mean PPD reduction (1.4 mm), CAL gain (1 mm), and MSBI scores. BANA Test, scores were co-relative with the clinical findings indicating that feracrylum group clearly outperformed the placebo group (<0.05) Conclusion: The results clearly indicate the significance of Feracrylum, in non-surgical Periodontal therapy, in patients undergoing anti-coagulant therapy for miscellaneous cardiovascular disorders